Hyperreactivity of the bronchi in children, whooping cough convalescents - Yu. V. Nesterova; A. V. Orlov; I. V. Babachenko (Журнал инфектологии)
Objective: to assess the presence and degree of bronchial hyperreactivity in convalescents of whooping cough based on the results of bronchial provocation tests.Materials and methods. Using bronchial provocative samples with a 0,02/0,33% histamine solution and 0,33% methacholine solution on a PROVOTEST-2 apparatus from PARI, bronchial hyperreactivity was studied in 12 pertussis convalescents aged 7 to 17 years. The level of endogenous nitrogen monoxide in exhaled air (FeNO) was measured using a portable NObreath electrochemical analyzer (from Bedfont Scientific Ltd.).The results. According to the results of BPP, 6 of 12 convalescents of whooping cough were found to have bronchial hyperreactivity of varying degrees. When conducting a breath test with a histamine solution, bronchial hyperreactivity was recorded in three children, in a sample with methacholine, in five. In 3 out of 6 children with revealed signs of bronchial hyperreactivity, the history of atopy was not burdened, which suggests a connection between the pertussis and the development of bronchial hyperreactivity. A significant increase in the level of endogenous nitric monoxide (above 16 ppb) was observed in 2 out of 10 patients. Follow-up observation showed that the duration of cough with whooping cough ranged from 3 to 6 months, and in patients with positive results of several tests it was maximum. Two out of three children with bronchial asthma showed elevated levels of FeNO and samples with methacholine. Follow-up observation showed that whooping cough aggravated bronchial asthma and demanded correction therapy.Conclusion. A pilot study on the evaluation of bronchial provocative tests suggests that the formation of bronchial hyperreactivity in convalescents of whooping cough is probable, including without a history of atopy, which increases the risk of developing bronchial asthma, however, additional studies are required for a final conclusion.